041 Making Recommendations About Diagnostic Tests And Strategies: What Do Experts Say?. (15th August 2013) - Mustafa, R; Brozek, J; Wiercioch, W; Ventresca, M; Lloyd, N; Schünemann, H
Abstract : Background: Current practices in developing guidelines about the use of diagnostic tests and strategies (DTS) are out of step with the conceptual discussion among experts. Objectives: Identify the essential factors to consider when making recommendations about DTS. Methods: We conducted semi-structured in-depth interviews with experts in assessing evidence and producing guidelines about DTS. Results: We interviewed 23 international experts. Although diagnostic test accuracy (DTA) was the factor most commonly considered by organisations when developing recommendations, experts agreed that DTA is never sufficient and may be misleading. Experts identified the following additional essential factors in making decisions about DTS: resource implications, complications, inconclusive results, additional benefits of the test, diagnostic/therapeutic impact, safety, feasibility, ethical, legal, and organisational considerations, patients' and societies' values and preferences and the link between the test results and patient important outcomes. Because direct evidence on DTS's effects on patient outcomes and resource implications is frequently unavailable, most experts agreed that decision analysis and mathematical modelling will be useful, but their opinion varied about the extent of details needed. Discussion: Formal decision modelling can be a useful framework for organising the clinical, cost, and preference data relevant to the use of diagnostic tests. Although it requires resources, it is useful for integrating these factors into decision making, identifying evidence gaps, and high priority research areas. Implications: Developing guidelines about the use of DTS requires considering factors beyond solely DTA but implementing this demand is challenging. Further development and testing of a framework that can guide this process is needed.